Creating Sustainable Competitive Advantage- A Resource-Based View: Case Studies of Bloomberg L.P and Reuters Group - Tsang, Simon Chi Kin (2006)
This paper investigates the requirements of creating sustainable competitive advantages for financial information industry from a resource-based view perspective. It proposes an instrument to determine the relevant strategic assets applicable in financial information industry to achieve sustainable competitive advantage. Although Bloomberg L.P has been in the financial information industry for only 22 years as compared to the 150 years history Reuters Group, its major competitor, the recent figures showed that Bloomberg has continued to grow its subscriber base through 2003 and into 2004 (Electronic Information Report, 2004). The loss of Reuters group's market share leads to a discussion of how company can achieve sustainable competitive advantage in the market place. The resource-based view of the firm has emerged as a popular theory of competitive advantage as Barney (1991) wrote that "firm is said to have a sustained competitive advantage when it is implementing a value creating strategy not simultaneously being implemented by any current or potential competitors and when other firms are unable to duplicate the benefit of this strategy" (Barney, 1991). Moreover, resources that are sources of sustainable competitive advantage are called strategic assets (Amit & Schoemaker, 1993; Barney, 1991).